2014
DOI: 10.1371/journal.pone.0091797
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Limit of Simultaneous Temporal Processing: How Many Concurrent ‘Clocks’ in Vision?

Abstract: A fundamental ability for humans is to monitor and process multiple temporal events that occur at different spatial locations simultaneously. A great number of studies have demonstrated simultaneous temporal processing (STP) in human and animal participants, i.e., multiple ‘clocks’ rather than a single ‘clock’. However, to date, we still have no knowledge about the exact limitation of the STP in vision. Here we provide the first experimental measurement to this critical parameter in human vision by using two n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
4
13
0
Order By: Relevance
“…Also, our findings are relevant for studies in the context of time perception. The effective number of flickering discs that were integrated—around two to four items presented in different spatial locations—might reflect the maximum number of temporal events that can be tracked simultaneously [ 32 , 33 ]. The ensemble representation of visual flicker may be critical for the parallel perception of multiple temporal signals.…”
Section: Discussionmentioning
confidence: 99%
“…Also, our findings are relevant for studies in the context of time perception. The effective number of flickering discs that were integrated—around two to four items presented in different spatial locations—might reflect the maximum number of temporal events that can be tracked simultaneously [ 32 , 33 ]. The ensemble representation of visual flicker may be critical for the parallel perception of multiple temporal signals.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that attentional selection plays a role in the processing of multiple durations. A study by Cheng, Yang, Han, Ding, and Fan (2014) showed that human observers are able to process up to four multiple durations at once. Furthermore, duration tracking performance dropped steadily when attention had to be spread over a larger amount of different duration stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of attention in the selective encoding of duration, it is likely that attentional limits dictate the extent to which multiple durations can be effectively selected. In line with this idea, several studies have reported behavioral detriments when processing multiple, temporally overlapping durations (Ayhan, Revina, Bruno, & Johnston, 2012;Cheng et al, 2014;Morgan, Giora, & Solomon, 2008;van Rijn & Taatgen, 2008). Together with the current results, these findings point towards attentional limits in the encoding of duration, suggesting that duration processing is an effortful process with a limited capacity.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study demonstrated localized duration compression following adaptation to the non-temporal features (i.e. orientation) of visual stimuli (Cheng et al, 2014). While we designed our experiments to reduce adaptation to non-temporal features by introducing spatial separation of adaptation and test stimuli, it is possible that some adaptation to non-temporal features occurred.…”
Section: Discussionmentioning
confidence: 99%